PENINGKATAN KINERJA GURU DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK SDN 3 TELUK MELANO - Almizan Almizan (Universitas Tanjungpura, 2022)
To improve the performance and insight of teachers in learning at SDN 3 Teluk Melano, the school conducted an action research. This study involved the principal as the primary school supervisor along with all the teachers at SDN 3 Teluk Melano to identify learning problems. The results of the discussion obtained the following solving steps: (1) holding a short workshop on the preparation of learning, implementation, and assessment of learning in schools, (2) carrying out collaborative educational supervision periodically by emphasizing the provision of assistance for learning improvement. The results of the study show the following: (1) Improved teacher performance in preparing lesson plans, (2) Improved teacher performance in carrying out learning, (3) Improved teacher performance in assessing learning achievement, (4) Improved teacher performance in implementing actions further results of student achievement assessment